1988
DOI: 10.1007/bf00609239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clonidine on beta-endorphin, ACTH and cortisol secretion in essential hypertension and obesity

Abstract: The role of alpha 2-adrenoceptor stimulation by clonidine on the secretion of beta-endorphin, ACTH, and cortisol in essential hypertension and obesity was studied in 45 subjects: 15 non-obese hypertensives, 10 obese hypertensives, 11 obese normotensives, and 9 healthy subjects. The circadian rhythm of plasma beta-endorphin, ACTH, and cortisol was determined after placebo and after three days on clonidine 0.45 mg daily. Clonidine lowered the blood pressure and blood ACTH and cortisol levels in all the subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, Facchineni et al found that dexamethasone failed to suppress hyperendorphinemia in obese patients (35,36). Administration of clonidine for 3 days to obese normotensive subjects was found to reduce cortisol and ACTH but did not alter elevated Bendorphin levels (108).…”
Section: Endogenous Opioidsmentioning
confidence: 98%
“…However, Facchineni et al found that dexamethasone failed to suppress hyperendorphinemia in obese patients (35,36). Administration of clonidine for 3 days to obese normotensive subjects was found to reduce cortisol and ACTH but did not alter elevated Bendorphin levels (108).…”
Section: Endogenous Opioidsmentioning
confidence: 98%